2023
DOI: 10.3389/fpsyg.2022.1084424
|View full text |Cite
|
Sign up to set email alerts
|

The more academic burnout students got, the more problematic mobile phone use they suffered? A meta-analysis of mainland Chinese adolescents and young adults

Abstract: IntroductionIn recent years, the relationship between academic burnout (AB) and problematic mobile phone use (PMPU) has become the hot issue of scholars, and a lot of related research has been carried out, but the results are different. Most studies showed that there was a significant positive correlation between AB and PMPU. However, some studies showed that the relationship between AB and PMPU was not significant. While this study aimed at exploring the relationship between AB and PMPU, as well as the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 125 publications
1
4
0
Order By: Relevance
“…Secondly, our findings suggest that perceived discrimination is a strong predictor of learning burnout, which in turn significantly predicts mobile phone addiction among higher vocational college students. In line with previous research suggesting the notion that negative responses to daily stressors induce academic burnout among students 34,35 and the close positive relationship between learning burnout and problematic mobile phone use, 38 our research supports the compensatory internet use theory. According to this theory, individuals who perceive themselves in a disadvantageous position (eg, discrimination) always exert mental exhaustion and learning burnout, and finally, these negative situations cause individuals to tend to (excessively) the internet to compensate for their negative emotions, resulting in mobile phone addiction.…”
Section: The Impact Of Perceived Discrimination On Mobile Phone Addic...supporting
confidence: 91%
See 2 more Smart Citations
“…Secondly, our findings suggest that perceived discrimination is a strong predictor of learning burnout, which in turn significantly predicts mobile phone addiction among higher vocational college students. In line with previous research suggesting the notion that negative responses to daily stressors induce academic burnout among students 34,35 and the close positive relationship between learning burnout and problematic mobile phone use, 38 our research supports the compensatory internet use theory. According to this theory, individuals who perceive themselves in a disadvantageous position (eg, discrimination) always exert mental exhaustion and learning burnout, and finally, these negative situations cause individuals to tend to (excessively) the internet to compensate for their negative emotions, resulting in mobile phone addiction.…”
Section: The Impact Of Perceived Discrimination On Mobile Phone Addic...supporting
confidence: 91%
“…37 Specifically, individuals' response to negative life situations is the reason for compensatory internet use, and the response can compensate for negative emotions by using the internet to generate positive feelings. 38 Higher vocational college students often experience negative feelings in learning, such as feelings of exhaustion and burnout, resulting in a decline in academic performance, so they tend to use mobile phones excessively to alleviate the burnout, resulting in mobile phone addiction.…”
Section: The Mediating Effect Of Learning Burnout Between Perceived D...mentioning
confidence: 99%
See 1 more Smart Citation
“… 43 , 44 MPD as a result of learning burnout, previous studies have shown that learning burnout and MPD can damage the sense of social support, specifically leading to a reduction in school participation and family closeness. 45 Therefore, if adolescents are not provided with adequate social support, their learning burnout will not be alleviated, which indirectly leads to MPD. Although both the theoretical underpinnings and the empirical research supported a pin-point correlation between MPD, learning burnout and social support, there is a lack of known about the mediating role of adolescents’ social support in the relationship between learning burnout and MPD.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that more than 30% of primary school students experienced learning fatigue, while the percentage increased to more than 70% among secondary school students, reflecting a higher prevalence of learning burnout (Gao, 2023). Learning burnout is known to be associated with various negative consequences, such as heightened levels of depression and anxiety, physical symptoms, internet addiction, and a greater likelihood of school dropout (Li et al, 2023; Qin et al, 2023; Walburg, 2014). Depression is now the most common psychological problem among adolescents.…”
Section: Introductionmentioning
confidence: 99%